2007
DOI: 10.1186/1743-422x-4-36
|View full text |Cite
|
Sign up to set email alerts
|

Infection of hepatitis B virus in extrahepatic endothelial tissues mediated by endothelial progenitor cells

Abstract: Background: Hepatitis B virus (HBV) replication has been reported to be involved in many extrahepatic viral disorders; however, the mechanism by which HBV is trans-infected into extrahepatic tissues such as HBV associated myocarditis remains largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…dermatological disease, arthritis, glomerulonephritis, aplastic anaemia, neuropathy, vasculitis, myocarditis), and the virus has extensive reservoirs of extra-hepatic replication (e.g. lymph nodes, spleen, bone marrow, kidney, colon, stomach, skin, pancreas, brain, heart, lung) [Rong et al, 2007]. It is therefore conceivable that chronic HBV infection could upregulate the expression of hypoxia-inducible genes even in tissues other than the liver.…”
Section: Hbx Regulation Of Ca IX Expression In Human Hepatocellular Cmentioning
confidence: 99%
“…dermatological disease, arthritis, glomerulonephritis, aplastic anaemia, neuropathy, vasculitis, myocarditis), and the virus has extensive reservoirs of extra-hepatic replication (e.g. lymph nodes, spleen, bone marrow, kidney, colon, stomach, skin, pancreas, brain, heart, lung) [Rong et al, 2007]. It is therefore conceivable that chronic HBV infection could upregulate the expression of hypoxia-inducible genes even in tissues other than the liver.…”
Section: Hbx Regulation Of Ca IX Expression In Human Hepatocellular Cmentioning
confidence: 99%
“…Our previous study has showed that the EPCs derived from cord blood are capable of uptaking HBV, but not support the viral replication [16]. It is totally unknown whether MSCs are capable of uptaking HBV or permissive for HBV replication.…”
Section: Introductionmentioning
confidence: 99%
“…There are two hypotheses regarding HBV related myocarditis; one proposes an indirect mechanism with immune complexes (12), whereas the other proposes a direct myocardial cell injury by HBV. Some authors have reported that HBV proteins and nucleic acids were found in a number of non-hepatic tissues, including the myocardium (11,13). However, the acute heart failure in the present case was not myocarditis but myopathy because the serum levels of CK, which is a sensi- Figure 4.…”
Section: Discussionmentioning
confidence: 99%